"The Catholic Church has a big structure": Social movement activists and the role of local Catholic churches in Hong Kong and Ukraine within the civil societies - HERASYM, Halyna (Institutional Knowledge at Singapore Management University, 2024)
The general body of literature on the theology of liberation tends to focus either on ecclesiastical debate, theological intricacies, or discussion within the church. Not much attention is paid to the empirical investigation of how civil society members might be influencing the rhetoric of the local church. This article takes a different approach and explores how liberation movements in Ukraine and Hong Kong inform and inspire elements of the theology of social justice within local Catholic communities through bringing to life their social dreams and engaging the churches in action. Looking at how churches and activists interact in the aftermath of the Euromaidan and the Umbrella Movement, we explore how grassroots activists approach religious hierarchies and how, in these circumstances, the clergy of the churches might be pressured into maneuvering between the social dreams of civil society and the Vatican.